Pattern and annual rates of Scrobicularia plana mercury bioaccumulation in a human induced mercury gradient (Ria de Aveiro, Portugal) - Coelho, J. P. (2006)
Due to the lack of knowledge regarding annual bioaccumulation rates in estuarine and marine fauna, the main aim of this work was to study the annual mercury bioaccumulation in the well-documented bivalve species Scrobicularia plana along a human induced mercury gradient in the Ria de Aveiro coastal lagoon (Portugal) and in a nearby, non-polluted system (Mondego estuary), parallel to the risks associated with its consumption by humans.